Practical blockchain and cryptocurrency. (LiveLessons (Indianapolis, Ind.), 2022)
7 Hours of Video Instruction 7 hours of focused video training to teach core blockchain and cryptocurrency skills Overview Practical Blockchain and Cryptocurrency LiveLessons is your complete guide to learning and incorporating practical crypto and blockchain knowledge and skills for your company's systems. Unlike some other courses, Practical Blockchain and Cryptocurrency LiveLessons focuses on real-world applications, so you can learn with hands-on demos. In this course you will learn how to: Buy, trade, mine your own, and use cryptocurrency, including Bitcoin, Ripple, and DOGE Create your own blockchains for internal enterprise IT applications Create and execute your own smart contracts Learn how to perform cybersecurity audits on blockchains This course was built for anyone who wants to understand how popular cryptocurrencies work including Bitcoins and ETH, as well as professionals needing to implement their own blockchain applications or mine cryptocurrencies, and cybersecurity professionals who need to test and audit Blockchain applications. The course concludes with topics of modern cyber attacks in cryptocurrency and blockchain space. You will have the tools needed to test your own blockchain applications and understand how to protect them against future attacks. Expert author and trainer Aamir Lakhani will give you hands-on practical experience to become a blockchain and cryptocurrency engineer and architect. Topics include Module 1: Introduction to Cryptocurrencies Module 2: The Blockchain Module 3: Mining Module 4: Blockchain Applications Module 5: Cyber Attacks Module 6 Evolution of Cryptocurrency and Blockchains About the Instructor Aamir Lakhani is a leading senior security strategist. He is responsible for providing IT security solutions to major enterprises and government organizations. Mr. Lakhani creates technical security strategies and leads security implementation projects for Fortune 500 companies. Industries of focus include healthcare providers, educational institutions, financial institutions, and government organizations. Aamir has designed offensive counter-defense measures for the Department of Defense and national intelligence agencies. He has also assisted organizations with safeguarding IT and physical environments from attacks perpetrated by underground cybercriminal groups. Mr. Lakhani is considered an industry leader in creating detailed security architectures within complex computing environments. His areas of expertise include cyber defense, mobile application threats, malware management, Advanced Persistent Threat (APT) research, and investigations relating to the Internet's dark security movement. He is the author or contributor of several books and has appeared on FOX Business News, National Public Radio, and other media outlets as an expert on cybersecurity. Writing under the pseudonym Dr. Chaos, Mr. Lakhani also operates the popular security social media blog which is hosted at DrChaos.com. In its recent list of 46 Federal Technology Experts to Follow on Twitter, Forbes magazine described Aamir Lakhani as "a blogger, InfoSec specialist, super hero...and all-around good guy." Skill Level Beginner Learn How To Understand the basics of blockchain technology Work blockchain and cryptocurrencies Create and store cryptocurrencies Create NFTs Write and enforce smart contracts on blockchains Course requirement None Who Should Take This Course Anyone interested in learning about blockchain Pen testing or ed team for blockchain applications Blockchain Engineers and Architects for Enterprise IT organizations Cryptocurrency expert or advisor About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.